Novel Presentation of DMV-Associated Encephalitis in a Long-Finned Pilot Whale (Globicephala melas). (February 2021) - Wessels, Mark E.; Deaville, Robert; Perkins, Matthew W.; Jepson, Paul D.; Penrose, Rod; Rocchi, Mara S.; Maley, Madeleine; Ballingall, Keith T.; Dagleish, Mark P.
Summary: Cetacean morbillivirus (CeMV) is an important global cause of morbidity and mortality in cetacean populations, with four pathological presentations including non-suppurative encephalitis. We describe an unusual case of dolphin morbillivirus (DMV)-associated non-suppurative encephalitis in a long-finned pilot whale ( Globicephala melas ), in which the lesions were orientated on the periventricular white matter and comprised prominent multifocal syncytia formation in the absence of systemic lesions. DMV RNA was detected in brain tissue by qRT-PCR and immunohistochemistry for morbillivirus antigen yielded intense labelling of syncytia in periventricular sites, with sparse involvement of the deeper neuroparenchyma. The pattern of lesions raises the possibility of viral dissemination through the cerebrospinal fluid, as described for canine distemper virus, suggesting that similar pathogenic mechanisms may be implicated in lesion development. Further investigation is required to establish the pathogenesis of CeMV encephalitis and the behaviour of the virus within the central nervous system of cetaceans.